HASIL BELAJAR SEBAGAI OBJEK PENILAIAN: (Kognitif, Afektif, dan Psikomotorik) - Achmad Rasyid Ridha; Nur Ali Rahmatullah; Aidatun Nisrina Nurul Firdaus; Yoga Wicaksono (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
Assessment of learning outcomes is an important component in the educational process to measure learner performance in three main aspects, namely cognitive, affective and psychomotor. Cognitive aspects relate to intellectual skills such as knowledge, comprehension, analysis, synthesis and evaluation. Cognitive assessment is usually done through written tests, oral exams, or tasks that require problem solving. Affective aspects include students' attitudes, values, interests, and motivations, which are assessed through observation, questionnaires, or self-reflection. Meanwhile, the psychomotor aspect includes physical skills and coordination of movement, which are assessed through hands-on practice, demonstrations, or performance-based projects. Integrating the assessment of these three domains ensures a holistic evaluation of the learner's development. This approach also helps educators identify students' strengths and weaknesses so that they can design more effective learning. The main challenges in assessing learning outcomes include the difficulty n objectively measuring affective and psychomotor aspects and the need for valid and reliable instruments. Therefore, educators need to combine different assessment methods, both quantitative and qualitative, to get an accurate picture of student learning. Thus, the assessment of learning outcomes focuses not only on the end result but also on the learning process itself. This research aims to discuss learning outcomes as an object of assessment. The method used in this research is a qualitative approach with the type of library research.